2013
DOI: 10.1111/dme.12293
|View full text |Cite
|
Sign up to set email alerts
|

Improved antenatal detection of congenital anomalies in women with pre‐gestational diabetes: population‐based cohort study

Abstract: Antenatal detection of cardiovascular anomalies was higher in women with diabetes, suggesting that recommendations for enhanced cardiovascular scanning may improve detection. Greater awareness of the increased risk of anomalies in other organ systems is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 22 publications
(36 reference statements)
0
10
3
Order By: Relevance
“…However, we did not observe any difference in the TGA cohort in which terminations were few. Pregestational diabetes leads to more thorough follow up and a higher prenatal detection rate of congenital anomalies . We did not observe a significant difference in prenatal detection of UVH and TGA among mothers with pregestational diabetes; the numbers were, however, limited.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…However, we did not observe any difference in the TGA cohort in which terminations were few. Pregestational diabetes leads to more thorough follow up and a higher prenatal detection rate of congenital anomalies . We did not observe a significant difference in prenatal detection of UVH and TGA among mothers with pregestational diabetes; the numbers were, however, limited.…”
Section: Discussioncontrasting
confidence: 74%
“…Pregestational diabetes leads to more thorough follow up and a higher prenatal detection rate of congenital anomalies. 35 We did not observe a significant difference in prenatal detection of UVH and TGA among mothers with pregestational diabetes; the numbers were, however, limited. In agreement with previous studies, 36 CHD was associated with multiple pregnancies.…”
Section: Discussioncontrasting
confidence: 57%
“…The rate of congenital anomalies, which was 27.5% in our cohort, is considerable. It is high in comparison with other cohorts of women with pre‐existing diabetes in pregnancy, but lower than other groups which have reported rates as high as 50% . For example, Eriksen and colleagues conducted a systematic review and found that the prevalence of congenital malformations was 6.4% in women with Type 1 diabetes .…”
Section: Discussioncontrasting
confidence: 66%
“…For example, Eriksen and colleagues conducted a systematic review and found that the prevalence of congenital malformations was 6.4% in women with Type 1 diabetes [4]. By contrast, Newham and colleagues reported a prevalence rate of congenital malformations of 50.3% in the offspring of women with pre-existing diabetes [15]. The explanation for this is multifactorial.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we cannot exclude that we have missed diagnoses of fetal malformations in terminated pregnancies. Male sex has recently been identified as the only factor associated with a higher antenatal detection rate of congenital malformations . Against this background, we cannot exclude that the rate of abortions attributable to congenital anomalies is higher in pregnancies with male fetuses, leading to an underestimation of the risk for malformations.…”
Section: Discussionmentioning
confidence: 89%